Genomic evidence for three distinct species in the Erebia manto complex in Central Europe (Lepidoptera, Nymphalidae) - Amanda Jospin; Yannick Chittaro; Daniel Bolt; David Demergès; Kevin Gurcel; Jürgen Hensle; Andreas Sanchez; Christophe Praz; Kay Lucek (Conservation Genetics, 2023)
A problem to implement conservation strategies is that in many cases recognized taxa are in fact complexes of several cryptic species. Failure to properly delineate species may lead to misplaced priorities or to inadequate conservation measures. One such species complex is the yellow-spotted ringlet Erebia manto , which comprises several phenotypically distinct lineages, whose degree of genomic isolation has so far not been assessed. Some of these lineages are geographically restricted and thus possibly represent distinct units with conservation priorities. Using several thousand nuclear genomic markers, we evaluated to which degree the bubastis lineage from the Alps and the vogesiaca lineage from the Vosges, are genetically isolated from the widespread manto lineage. Our results suggest that both lineages are genetically as strongly differentiated from manto as other taxonomically well separated sibling species in this genus from each other, supporting a delineation of bubastis and vogesiaca as independent species. Given the restricted and isolated range of vogesiaca as well as the disjunct distribution of bubastis, our findings have significant implication for future conservation efforts on these formerly cryptic species and highlight the need to investigate the genomic identity within species complexes.